Anti-Inflammatory and Analgesic Evaluation of a Phytochemical Intercalated into Layered Double Hydroxide - Viviane A. Guilherme; Vanessa R. R. Cunha; Eneida de Paula; Daniele R. de Araujo; Vera R. L. Constantino (MDPI AG, 2022)
Coumaric acid (CouH), an antioxidant molecule assimilated by food consumption, was intercalated into layered double hydroxide (LDH) nanocarrier, having zinc and aluminium ions in the layers (LDH-Cou), to evaluate its pharmacological activity through in vitro and in vivo assays in mice. Therefore, the following tests were performed: coumarate delivery in saline solution, fibroblasts' cell viability using neutral red, peritonitis induced by carrageenan, formalin test, acetic-acid-induced writhing, and tail-flick assay, for the non-intercalated CouH and the intercalated LDH-Cou system. Furthermore, different pharmacological pathways were also investigated to evaluate their possible anti-inflammatory and antinociceptive mechanisms of action, in comparison to traditionally used agents (morphine, naloxone, caffeine, and indomethacin). The LDH-Cou drug delivery system showed more pronounced anti-inflammatory effect than CouH but not more than that evoked by the classic non-steroidal anti-inflammatory drug (NSAID) indomethacin. For the analgesic effect, according to the tail-flick test, the treatment with LDH-Cou expressively increased the analgesia duration (p < 0.001) by approximately 1.7-1.8 times compared to CouH or indomethacin. Thus, the results pointed out that the LDH-Cou system induced in vivo analgesic and anti-inflammatory activities and possibly uses similar mechanisms to that observed for classic NSAIDs, such as indomethacin.